The role of training in organizations : a comparative case study of employees and management perspectives - Polo, Federica; Cervai, Sara (International Society for the Study of Work & Organizational Values, 2018)
The transition to a more collaborative way of working brought a change in the role played by training in organizations, representing not exclusively a way to develop employees’ core competencies but also a strategic tool to govern team processes and organizational outcomes. As a consequence, training became a system embedded in the organizational context, developed on the basis of values, beliefs and practices commonly adopted within the organization. In this regard, the literature still lacks an in depth analysis of how training is perceived in the organization and how the perspectives of different members vary. Therefore, this article aims to fill this gap comparing and analyzing the meanings and values attributed to the training by management and employees. The analysis has been carried out through the implementation of the Training Culture Scale (TSC) that allows to point out the meanings and values of training at individual, team and organizational level. Employees’ characteristics, tenure in the organization, gender and level of education can be predictors of the different perception of training within the organization. The comparison between managers and employees perceptions allows companies to develop strategies to strengthen the Training Culture of the organization.
Keywords: fi=Tuotantotalous|en=Industrial Management|